The West's assistance to the former USSR and Eastern Europe - Hayns, Michael R. (British Nuclear Energy Society, 1994)
This paper, given at the BNES Conference on Thermal Reactor Safety Assessment, outlines the various reactor safety assistance programmes for the former Soviet Union and Eastern European countries, then gives some examples of specific projects in which the AEA and the UK are involved.
Conference paper.
Keywords: Nuclear power plants -- Safety measures -- International cooperation.; Nuclear power plants -- Risk assessment.; elektronické knihy; electronic books